2023
DOI: 10.1111/add.16224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of perioperative high‐dose transdermal nicotine patch on pain sensitivity among male abstinent tobacco smokers undergoing abdominal surgery: A randomized controlled pilot study

Abstract: Background and Aims Previous studies have focused on the role of perioperative nicotine replacement therapy (NRT) in improving the success rate of long‐term smoking cessation in tobacco smokers. This study aimed to measure the effectiveness of high‐dose NRT in alleviating postoperative pain for male abstinent smokers receiving abdominal surgery. Design This was a parallel‐group, randomized, double‐blind and controlled pilot trial. Setting and participants In total, 101 male smoking‐abstinent patients from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Nicotine plays a vital role in pain-related processes. Despite providing short-term pain relief, prolonged nicotine exposure leads to tolerance and increased pain sensitivity due to receptor desensitization and neural changes [26]. Seyedsadeghi et al indicated that there were no significant statistical disparities between the groups concerning pain intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine plays a vital role in pain-related processes. Despite providing short-term pain relief, prolonged nicotine exposure leads to tolerance and increased pain sensitivity due to receptor desensitization and neural changes [26]. Seyedsadeghi et al indicated that there were no significant statistical disparities between the groups concerning pain intensity.…”
Section: Discussionmentioning
confidence: 99%